Aplikasi Mobile JKN untuk Memudahkan Akses Pelayanan BPJS - Suhadi Suhadi; Jumakil Jumakil; Irma Irma (FORIKES, 2022)
Advances in information technology today have a broad impact on health services. The presence of information technology will facilitate services in the health sector. The purpose of this study was to determine the effect of using the